Pengaruh Penerapan Strategi Pembelajaran Quantum terhadap Interaksi Edukatif dan Hasil Belajar Peserta Didik Pada Pembelajaran Fiqih di Madrasah Tsanawiyah Negeri 1 Bengkalis - Marda Rahmatul Ula (Akademika: Jurnal Keagamaan dan Pendidikan, 2020)
Based on the preliminary observations, learning strategies used in fiqh subject at Madrasah Tsanawiyah Negeri 1 Bengkalis are traditional and rigid, so students only listen, see, and write what is instructed by the teacher in front of the class. The problem of this study is about the effect of using quantum learning strategy on students’ educational interaction and learning outcome in Fiqh subject at Madrasah Tsanawiyah Negeri 1 Bengkalis. This research was quasi experimental pre-test and post-test control group design. The subjects were all students in grade VII E and F. Quantum learning strategy was used on experimental (n = 32), and a control group (n = 32) using non quantum learning strategy. The result of paired sample t-test showed that there was an effect of significant difference of educational interaction and student learning outcome before and after using quantum learning strategy in the experimental group with significance of 0,000 < 0.05. Thus, there was a significant influence of using quantum learning strategy on students’ educational interaction and learning outcome in learning Fiqh at Madrasah Tsanawiyah Negeri 1 Bengkalis.